EFFECT OF COLD STORAGE TECHNIQUES ON FLOWER QUALITY AND VASE LIFE OF ROSE VAR SUN KING - R. J. MAKWANA,; ALKA SINGH,; P. NEELIMA, (The Bioscan, 2015)
Investigation was conducted to study the influence of cold storage(2ºC) techniques comprising of seal packaging with polypropylene (PP 24μ), butter paper (52μ), holding in 200 mgL-1Al2(SO4)3 vase solution, holding in vase (distilled water) and without any packaging and without holding in vase water in rose cut flowers var. Sun King. After ten days of cold storage, the stored flowers were held in distilled water and compared with fresh flowers as control. Among all the treatments, the polypropylene packaged cold stored cut roses showed promising result with highly retained post harvest quality at the end of 10days storage period that were at par with fresh flowers. The PP packaged cold stored rose cut flowers were almost at par with fresh cut roses and showed significantly higher water uptake (58.7mL) and retained fresh weight (8.76 %) along with retained carotene pigment content (3.76 mg/g fw) in the petal tissue as over other treated stored flowers. Further, the same treatment showed higher bud length (5.23 cm) and flower diameter (6.37cm) with higher membrane stability index (57.07%) of the petal tissue as well as higher post storage vase life (4.73 days) as compared to all treatments (1.07 to 3.03 days vase life) and these cold stored flowers were at par with the fresh flowers in terms of flower diameter (6.53 cm) and vase life (4.83 days).